OUTCOME OF SIX MONTHS OF YOGIC PRACTICES ON PSYCHOLOGICAL PARAMETERS IN PATIENTS SUFFERING FROM HYPOTHYROIDISM - Chawla Ranjna; Nair Rukamani; Mukherjee Somnath; Meitei Yendrembam Ibotombi; Sood V R (International Journal of Applied Ayurved Research, 2020)
Aim: To see the effect of Yoga on thyroid function tests, quality of life [WHO-QOL-BREF (WHO quality of life Brief version)], depression [BDI-II (Beck Depression Inventory)] and quality of sleep [PSQI (Pittsburgh sleep quality index)] at baseline and after 3 and 6 months of intervention. Methods and Material: Out of the 100 hypothyroidism patients recruited, 83 completed the trial (41 in control group and 42 in Yoga group). The control group was given Thyroxine re-placement therapy while Yoga group received Yoga along with Thyroxine replacement. Yoga sessions were of 45 minute and were given thrice a week for the first 2 months and twice in a week for the next 4 months. Results: In Yoga group, significant improvement of quality of life for domain I (Physical) [p=0.001(from baseline to 6th month) and p=0.002 (from 3rd to 6th month)] and domain II (psychological) [p=0.045 (baseline to 3rd month) and p= 0.000 (baseline to 6th month)] was observed. Participants in both groups demonstrated significant improvement (p≤0.001) in BDI-II score from their baseline values but Yoga group also showed significant improve-ment when compared to control group after 6 months (p=0.002). At baseline, Global Pitts-burgh Sleep (GPS) quality in control group was better (p=0.03) as compared to Yoga group. After intervention therapy improvement was seen in both the groups (In control group p= 0.039 after 3 months and p=0.001 after 6 months, in Yoga group p ≤0.001 after 3 and 6 months). More improvement was seen in the Yoga group as compared to control group (p=0.000 after 3 and 6 months). Individual sleep Component for Sleep duration showed im-provement only in Yoga group after 3 months (p= 0.03). Use of sleeping medication compo-nent showed significant decrease in control group (p=0.014). A significant increase in fT4 and significant reduction in TSH was observed in both the groups. In Yoga group levels of TSH were found to be in normal physiological range. Conclusion: Yoga was effective in controlling quality of life in physical and psychological domain, improving sleep quality and reducing depression in hypothyroidism patients.